Fungsi Pantun dalam Kesenian Tundang pada Masyarakat Melayu di Kabupaten Mempawah Kalimantan Barat - Sri Kusnita; Muhammad Lahir (Mahesa Research Center, 2022)
This paper aims to describe and analyze the function of pantun in tundang art in the Malay community in Mempawah Regency. This research uses descriptive qualitative method. The data in this study are rhymes in Tundang art obtained from informants, namely the Mempawah Malay community who know the intricacies of rhymes in tundang art and analyzed based on the function of rhymes in the lives of the Malay people of West Kalimantan. Data collection techniques used in this research are documentary study techniques and direct communication techniques. The results showed that the pantun in Tundang art in the Mempawah Malay Society of West Kalimantan serves as a tool to 1) educate because in the Tundang art poem in the Mempawah Malay Society of West Kalimantan there is advice to always be grateful, work together, have a sense of unity, and must always act. good; 2) disclose the customs including the marriage customs of the Mempawah Malay community; 3) entertaining because the rhymes in tundang art use instrument music to accompany the rhyme chants which function to make it more beautiful so that the audience feels entertained; 4) delivery of social criticism because rhymes in tundang art include social criticism for the community.